Labuan IOFC offshore banking and industry: the growth through product/service innovation - Airulamri Amran; Mohd Faisol Ibrahim; Geoffrey H. Tanakinjal; Lo, Bryan Ching Wing (Universiti Malaysia Sabah, 2006)
Labuan IOFC is an International financial center located at the "positioned center" of the Asia-Pacific basin. The center is moving ahead to become a premier offshore financial center in the world. In the mean time, it promotes more activities and services to a great extent a truly integrated service provider center. Hence, new activities and innovative products are continuously being developed in Labuan which will benefit investors and other offshore players. It offers wide range of offshore financial products and services and complements Kuala Lumpur as a regional financial center. Besides, the legislative framework is not only business friendly but also prudent to safeguard Labuan's reputation and image as offshore financial center. The main objective of this research is to identify the growth of financial products and services in labuan IOFC Offshore Banking Industry. The significance of the research indudes contributing the direction of marketing financial products and services and attracting customers that has changed through the growth of financial product and service innovations. Through product and service innovations, the offshore bankers may consider the key product and service to achieve competitive edge. Moreover, by conducting this research, Labuan and national economy may be improved through better financial services and higher profit from the offshore banking industry.